1995
DOI: 10.1136/pgmj.71.841.702
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemia induced by paracetamol

Abstract: Hyperglycaemia induced by paracetamolSir, Hypoglycaemia is a well-recognised feature of paracetamol overdose, after the development of fulminant hepatic failure, but we are aware of only one previous description of hyperglycaemia and that was in a patient with a family history of diabetes mellitus.'Over recent months we have seen five patients, all male, aged 17 to 40, who have had random blood sugars of 7.2-12.8 mmol/l (mean 9.1 mmol/l) at the time of their initial paracetamol level, taken 6-12 h after the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Elevated levels of three blood analytes that are routinely associated with liver damage in vertebrates were registered in snakes in the APAP group: GLU 22,23 , AST 24 , and ALT 25 . These results suggest that APAP-treated snakes experienced hepatoxicity, although in a previous study conducted at NWRC, no hepatic injury was noted on histopathological examination of liver samples collected from brown treesnakes that had died from oral administration of 80 mg APAP (P. Savarie, NWRC, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of three blood analytes that are routinely associated with liver damage in vertebrates were registered in snakes in the APAP group: GLU 22,23 , AST 24 , and ALT 25 . These results suggest that APAP-treated snakes experienced hepatoxicity, although in a previous study conducted at NWRC, no hepatic injury was noted on histopathological examination of liver samples collected from brown treesnakes that had died from oral administration of 80 mg APAP (P. Savarie, NWRC, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…There are several case reports that describe the finding of acute hyperglycaemia in paracetamol overdose. [1][2][3][4] This is often explained by concurrent hepatotoxicity. The mechanism for this is unclear but a direct effect of paracetamol or its metabolites on the pancreas, or the body's response to stress hormones, have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for this is unclear but a direct effect of paracetamol or its metabolites on the pancreas, or the body's response to stress hormones, have been proposed. 2 Animal studies have indicated that paracetamol depletes glycogen, as well as glucathione, and glycogen depletion correlates with hyperglycaemia. 5 There are also animal studies that demonstrate changes in pancreatic beta cell ultrastructure that would account for glycaemic disturbances.…”
Section: Discussionmentioning
confidence: 99%